Digital-Based Academic Evaluation Efficiency: The Roles of Learning Analytics, Educational Management Information Systems, and Principals' Digital Managerial Competence - Rosdiana; Heny Fitriani; R. Dewi Mutia Farida (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study examines the associations of learning analytics, Educational Management Information Systems (EMIS), and principals’ digital managerial competence with digital-based academic evaluation efficiency in senior high schools. It addresses the need to transform academic evaluation from manual and fragmented practices into integrated, accurate, and data-driven processes. Methods – A quantitative explanatory cross-sectional design was employed using survey data from 150 principals, vice principals, teachers, and academic administrative staff in senior high schools in Serang, Banten. Data were collected using a five-point Likert scale and analyzed through multiple linear regression using EViews after establishing the validity, reliability, and suitability of the data for regression analysis. Findings – Learning analytics and EMIS were positively and significantly associated with digital-based academic evaluation efficiency by supporting systematic data use, integration, reporting accuracy, and administrative efficiency. Principals’ digital managerial competence showed the strongest statistical association, highlighting the importance of digital leadership, coordination, and data-driven decision-making. The model explained 70.2% of the variance in academic evaluation efficiency. Research implications – Efficient digital-based academic evaluation requires the alignment of analytical capacity, information system quality, and principals’ digital managerial competence. These findings provide practical guidance for strengthening evidence-based academic governance and accountability in digitally transforming secondary schools. Originality – This study integrates learning analytics, EMIS, and principals’ digital managerial competence within a single framework to explain digital-based academic evaluation efficiency, addressing a gap in previous studies that examined these factors separately.